PENGARUH PEMBERIAN PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL SELADA (Lactuca sativa L. VAR. Crispa) - Hanan, Ridwan; Meriyanto; Buyana, Nova Tri; Ladina, Julia Echa (University of Prof. Dr. Hazairin, SH, 2024)
The focus of this study was to evaluate the impact of applying liquid organic fertilizer (Eco-Farming) on the growth and yield of lettuce plants. The research location includes the experimental garden land of the Faculty of Agriculture, Tridinanti University, Palembang, located in Pulau Semambu Village, North Indralaya District, Ogan Ilir Regency, South Sumatra Province. The study took place from July to October 2023, using an experimental method with Group Randomized Design (RAK) involving 5 treatments and 5 repeats. In each experimental or mapped unit, there are 80 plants, with a total sample of 3 sample plants analyzed. The tested treatment involved P0 as a control (without liquid organic fertilizer), P1 with 5 ml of Liquid Organic Fertilizer (POC) per liter of water, P2 with 10 ml of POC per liter of water, P3 with 15 ml of POC per liter of water, and P4 with 20 ml of POC per liter of water. Variables observed include plant height (cm), number of leaves (strands), root volume (cm3), wet pruning weight (g), and plant dry weight (g). The results showed that the application of liquid organic fertilizer 'Eco-Farming' had a positive impact on the growth and yield of lettuce plants. In the P4 treatment (20 ml POC/L water), the plant height reached 17.3 cm, with the number of leaves as much as 7.9 strands at the age of 4 weeks, and the weight of wet pruning per plant reached 14.15 g.